Sample size correction factors for indentation on asphalt bitumens. (15th November 2017) - Filonzi, Angelo; Delgadillo, Rodrigo
Highlights: Sample size effects for indentation on asphalt bitumens are calculated. Results are based on elastic viscoelastic transformations and load superposition. Effects are significant for sample sizes commonly used in bitumens' indentation. The influence of sample depth is higher than the lateral size effect. Sample size correction factors are provided for finite depth and diameter. Abstract: Closed form solutions for obtaining fundamental properties of viscoelastic materials through indentation assume a semi-infinite indented media. For real sample sizes, proper material characterization requires determining the effect of finite sample dimensions. Available solutions from the literature were used to obtain correction factors for finite sample depth. Since no solutions were available for laterally confined viscoelastic materials, correction factors were developed in this work, assuming null displacement at the confined lateral edges and applying load superposition. Both correction factors were obtained for axisymmetrical samples indented with conical, cylindrical and spherical geometries. Two asphalt binders commonly used in road paving were tested in indentation with spherical geometry at intermediate temperature. Significant correction factors were needed for sample sizes commonly used in penetration testing of bitumens. The effects of sample dimensions resulted in underestimations of 19% and 22% in the creep compliances of each bitumen. Based on the results, minimum sample sizes required to make the boundary conditions effects' negligible are recommended for common asphalt binders indented at intermediate temperatures.